Human smuggling in the Eastern Mediterranean - Baird, Theodore (Routledge studies in criminal justice, borders and citizenship, 2017)
Introduction -- A state of transformation -- Conflict and quasi-states -- Policing tensions, intermezzo: dynamic cycles -- Helmets, books, and money -- Decisions and relations -- Coercion, violence, and vulnerability -- Conclusion